AN ANALYSIS OF CONVERSATIONAL IMPLICATURE OF THE CHARACTERS IN THE BIRD BOX FILM - Kelvin Kelvin; Zia Hisni Mubarak (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
. To accomplish the goals of an ability to understand, it is anticipated that everyone involved in the communication process will work together. However, in practice, sending purposes are not usually expressed clearly. In reality, a person might not reach the part of the conversation where they are required to speak openly, intelligibly, pertinently, and appropriately so that the other person can understand them incredibly well. This phenomenon is referred to as conversational implicature in linguistic terms, where individuals prefer to indicate their additional or hidden meaning that is delivered behind spoken words. By using Grice's theory to determine implicature form for portraying conversation context, which determines the factors that influence communication, this research aims to examine the phenomenon in the conversation of the two main characters in the Bird Box film. The researcher used the conversational implicature theory by Grice (1975) to identify the utterance and the speech acts theory by Searle (1976) to categorize the function. Searle (1976) classified speech acts identified are representatives/assertives, instructions, commissives, expressives, and declarations. This study has a qualitative research design. The researcher employed the Sudaryanto (2015) interview method to gather data, the Sudaryanto (2015) pragmatic identity method to analyze the data, and the Sudaryanto (2015) informal presentation approach to convey the research findings. The researcher gathered ten data sets with conversational implicature in order to examine the data.